2006
DOI: 10.1111/j.1467-789x.2006.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and socioeconomic risk factors of obesity among urban female students in Al‐Khobar city, Eastern Saudi Arabia, 2003

Abstract: The aim of this study was to determine the prevalence and the socioeconomic risk factors associated with obesity among female school-aged children and adolescents in primary and intermediate schools in Al-Khobar city, Kingdom of Saudi Arabia. This is a cross-sectional study conducted in Al-Khobar city, which is located in the eastern part of Saudi Arabia, during the period of January to March 2003. It involved 2239 female schoolchildren randomly selected from 30 regular government and private primary and prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
42
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 45 publications
12
42
1
Order By: Relevance
“…In our work, high maternal education was a protective factor for obesity, this was consistent with some previous studies which suggested that low maternal education was a risk factor for childhood obesity [5,8], however, this result conflicted with the results from other studies, in which overweight and obesity was more prevalent among children with highly educated mother [1,18]. Controversial results may arise from differences in the design of the study, such as characteristics of participants, methodology, and sample size.…”
Section: Discussionsupporting
confidence: 55%
“…In our work, high maternal education was a protective factor for obesity, this was consistent with some previous studies which suggested that low maternal education was a risk factor for childhood obesity [5,8], however, this result conflicted with the results from other studies, in which overweight and obesity was more prevalent among children with highly educated mother [1,18]. Controversial results may arise from differences in the design of the study, such as characteristics of participants, methodology, and sample size.…”
Section: Discussionsupporting
confidence: 55%
“…For associated factors 31% prevalence of mothers of the non obese school children with low education, 23.76% prevalence of non obese children in upper socioeconomic status and 17% prevalence of non obese children of working mothers (expected frequency of disease among non diseased) was considered. 19 The final sample size was given by the variable mothers' education because it gave the largest sample of all the independent variables. To see the association of mothers education with the obesity in children we took a confidence level of 95%, power of 80%, the ratio of exposed children (whose mothers are illiterate) to unexposed children (children whose mothers have at least five years of education) and the prevalence of obesity among children of educated mothers of 31% the sample size came to be 336 with 114 in unexposed arm and 228 among exposed arm.…”
Section: Methodsmentioning
confidence: 99%
“…Computer use, television watching 9 for long periods of time and especially at the prime time when most food advertisements are shown. 16,17 Obesity in children is also become a public health problem in countries like India has significant rise in the proportion of overweight and obese children has taken place, especially in the urban centers; 18 Saudi Arabia has prevalence of overweight and obese school children boys 20% and girls 11% 19 and other countries in the gulf also have similar trends, for instance, about 16.5% and 16.9% of boys and girls, respectively are obese and overweight in United Arab Emirates. 20 The study helped to formulate the recommendations for preventing the growing epidemic of obesity and factors related to it in a typical local setting.…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with previous studies. 44,46 The current study detected a significant association between glycemic control and the patient 's functional status. This result agreed with Rita et al, who found a similar association between uncontrolled diabetes and functional disabilities.…”
Section: Discussionmentioning
confidence: 84%